Konsep Kenajisan Orang Musyrik dalam Al-Qur’an (Surat Al-Taubah Ayat 28) - Happy Saputra; Zaipuri Zaipuri (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2020)
After Fath of Mecca, polytheists are forbidden to perform hajj and umrah. More precisely this prohibition took effect in the year 10 H. This prohibition began with the granting of unclean status for the polytheists. This article will conduct a study of the uncleanness of the polytheists who are conceptualized in the QS. al-Taubah (9): 28. This study was conducted with the assumption that al-Qur'an is present in the locality of the Arabian peninsula. The formulation of the problem of this study is how the context of the decline in QS. al-Taubah (9): 28 and how the commentators interpret the verse. The results of this study indicate that the QS. al-Taubah descended on Mecca in 9 H. At that time Mecca was already controlled by Muslims and began to be sterilized by the polytheists. So that the polytheists were forbidden to perform Hajj and Umrah or forbidden to enter the city of Mecca at all. Then, the majority of commentators interpret that the uncleanness of the polytheists is due to the shirk that is in him. In addition, the ban also resulted in the population of Mecca being worried about the impact on trade. However, Allah gave sufficiency to the population of Mecca with rain falling, residents in areas around Mecca who converted to Islam. Pasca fath al-Makkah, orang-orang musyrik dilarang untuk melaksanakan haji dan umrah, lebih tepatnya berlaku pada tahun 10 H. Pelarangan ini bermula dari pemberian status najis bagi orang-orang musyrik. Artikel ini akan melakukan kajian tentang kenajisan orang musyrik yang terkonsep dalam QS. al-Taubah (9): 28. Kajian ini dilakukan dengan asumsi bahwa al-Qur’an hadir dalam lokalitas jazirah Arab. Tulisan ini akan mengkaji bagaimana konteks turunnya QS. al-Taubah (9): 28 dan bagaimana penafsiran atas ayat tersebut. Adapun hasil kajian ini menunjukkan bahwa QS. al-Taubah turun di Mekah tahun 9 H. Ketika itu, Mekah sudah dikuasai oleh umat Islam dan mulai dilakukan sterilisasi dari orang-orang musyrik. Sehingga orang-orang musyrik dilarang untuk melakukan haji dan umrah atau dilarang memasuki kota Mekah sama sekali. Mayoritas mufasir menafsirkan bahwa kenajisan orang-orang musyrik adalah karena kesyirikan yang ada di dalam dirinya. Selain itu, pelarangan tersebut juga berakibat pada penduduk Mekah khawatir atas imbasnya pada perdagangan. Akan tetapi, Allah memberi kecukupan pada penduduk Mekah dengan hujan yang turun, sehingga penduduk di daerah-daerah sekitar Mekah masuk Islam.